A NOMENCLATURAL AND CULTURAL NOTE ON CHLORELLA PERUVIANA G. CHACÓN AND OTHER SPECIES OF THE GENUS CHLORELLA BEIJ. (CHLORELLACEAE, CHLORELLALES) - Calvo-Pérez Rodó, Juan Diego (2015)
On the course of our investigations on the culture of Chlorella peruviana G. Chacón, it becameapparent that some nomenclatural changes were necessary within the genus. Here, we presentthose changes: transfer of C. pyrenoidosa H. Chick to Auxenochlorella as A. pyrenoidosa (H. Chick) Molinari & Calvo-Pérez comb. nov.; the replacement name C. gloriae Molinari nom. nov. for C. salina Butcher; and the lectotypification of C. peruviana G. Chacón. Finally, the liquid medium Calderón for marine algae is validated for this last species.